2018
DOI: 10.3389/fmicb.2018.03174
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 Regulated Poly I:C-Induced Neutrophil Extracellular Traps and Acute Lung Injury Partly Through p38 MAP Kinase

Abstract: Acute lung injury (ALI) is the leading cause of morbidity and mortality in critically ill patients. Neutrophil extracellular traps (NETs) have been well documented in the ALI model of bacterial infection. In the present study, we demonstrated that poly I:C could induce pulmonary NETs. Upon poly I:C intratracheal inoculation, neutrophil infiltration in the bronchoalveolar lavage fluid (BALF) was significantly increased. Furthermore, the inflammatory cytokines IL-1β, IL-6, and TNF-α in the lung were also signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 54 publications
3
45
0
Order By: Relevance
“…We demonstrated markedly elevated baseline NET levels in PMNs isolated from COVID-19 patients, whereas PMNs isolated from healthy adults remained unaltered under basal conditions ( P = .0012; Figure 2B-C ). We also demonstrated that PMA, a nonphysiologic agonist, induced NETs in vitro by PMNs isolated from healthy adults, as previously reported, 23 but failed to further increase NET formation over the already high baseline in COVID-19 PMNs ( Figure 2B-C ). Although PMNs do not express Toll-like receptor 3 (TLR3), 24 , 25 we also found that poly(I:C), a damage-associated molecular pattern that typically signals through TLR3, induces NETs in PMNs isolated from COVID-19 adults and healthy donors (supplemental Figure 3).…”
Section: Resultssupporting
confidence: 90%
“…We demonstrated markedly elevated baseline NET levels in PMNs isolated from COVID-19 patients, whereas PMNs isolated from healthy adults remained unaltered under basal conditions ( P = .0012; Figure 2B-C ). We also demonstrated that PMA, a nonphysiologic agonist, induced NETs in vitro by PMNs isolated from healthy adults, as previously reported, 23 but failed to further increase NET formation over the already high baseline in COVID-19 PMNs ( Figure 2B-C ). Although PMNs do not express Toll-like receptor 3 (TLR3), 24 , 25 we also found that poly(I:C), a damage-associated molecular pattern that typically signals through TLR3, induces NETs in PMNs isolated from COVID-19 adults and healthy donors (supplemental Figure 3).…”
Section: Resultssupporting
confidence: 90%
“…In various disease models, DNase effectively degraded NETs and antagonized the effects of NETs 34 , 35 . A mouse model of laminectomy was established, and gross observation revealed that the scar formation was reduced in the mice treated with DNase I 30 days post operation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The powder of DNase I was diluted with physiological saline to 1 mg/ml, and the dosage for each mouse was 5 mg/kg (ref. 34 ). The diluted solution was absorbed with a gelatin sponge matching the size of the wound, and it was placed on the wound and then sutured.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, DNase alleviated BPD disease severity. A DNA backbone served as a scaffold for NETs; DNase degraded DNA and therefore diminished the functions of NETs 41 . DNase, which has been clinically approved for the treatment of cystic fibrosis 42 , warrants further examination in BPD therapy.…”
Section: Discussionmentioning
confidence: 99%